Intervensi Hukum Perkembangan Anak Usia Dini : Perlindungan Diri Dari Kekerasan Dan Eksploitasi - Churiyah Churiyah; Miftakhul Jannah; Yes Matheos Lasarus Malaikosa (Pusat Riset dan Inovasi Nasional, 2024)
Protection of early childhood children from violence and exploitation is a crucial issue that requires serious attention from various parties, including parents, educators and policy makers. This article discusses the legal interventions needed to protect young children from violence and exploitation. In this modern era, children face various risks that can threaten their physical, mental and emotional development. This research examines the existing legal framework in Indonesia, as well as international policies and regulations that aim to provide protection for children. In addition, this article evaluates the effectiveness of law implementation in the field and identifies the challenges faced in implementing child protection laws. Through a qualitative approach, data is collected from various sources, including case studies, interviews with legal experts, and analysis of legal documents. The research results show that despite progress in legislation, there are still gaps in legal implementation that need to be addressed. This article suggests concrete steps to strengthen protection mechanisms, raise public awareness, and involve various stakeholders in collective efforts to protect young children from violence and exploitation. This research emphasizes that early childhood protection must be a priority in the national development agenda. It is hoped that the implementation of comprehensive and sustainable intervention programs will be able to create a healthy, safe and prosperous young generation. Practical recommendations for stakeholders are presented as a guide in increasing the effectiveness of protecting children from violence and exploitation.